2015
DOI: 10.1111/jopr.12355
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Esthetic Impact of Smile Line in Complete Denture Wearers by Different Age Groups

Abstract: In this study, complete dental prostheses with smile lines that coincided with the cervical margins of the anterior teeth were the most acceptable. Less exposure of the maxillary teeth when smiling corresponded with decreased attractiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The overbite correction of adult patients should be performed with caution because as dentition gets older, the overbite decreases [10], and the use of intrusion mechanics for the anterior segment to decrease the smile arc and achieve the flattening or straightening of the smile has been associated with negative smile outcomes following orthodontic treatment [11]. Furthermore, the present study showed that reverse smiles were considered to be less attractive by laypeople, in agreement with Machado [4], who identified maxillary central incisor wear as an unesthetic quality.…”
Section: Discussionmentioning
confidence: 99%
“…The overbite correction of adult patients should be performed with caution because as dentition gets older, the overbite decreases [10], and the use of intrusion mechanics for the anterior segment to decrease the smile arc and achieve the flattening or straightening of the smile has been associated with negative smile outcomes following orthodontic treatment [11]. Furthermore, the present study showed that reverse smiles were considered to be less attractive by laypeople, in agreement with Machado [4], who identified maxillary central incisor wear as an unesthetic quality.…”
Section: Discussionmentioning
confidence: 99%
“…In prosthodontic treatment aesthetic plays a vital role in patients' satisfaction .Fabrication of a natural looking denture is not an easy task [9].The use of facial measurements as a guide for selection of anterior teeth for complete denture have been used in the past like interzygomatic distance, inner and outer canthus measurement, interalar, mouth and philtrum of upper lip widths and face length (Nasion-Gnathion) [1].…”
Section: Discussionmentioning
confidence: 99%